Cis-Cinnamic Acid Is a Novel, Natural Auxin Efflux Inhibitor That Promotes Lateral Root Formation. Issue 1 (11th November 2016) - Steenackers, Ward; Klíma, Petr; Quareshy, Mussa; Cesarino, Igor; Kumpf, Robert P.; Corneillie, Sander; Araújo, Pedro; Viaene, Tom; Goeminne, Geert; Nowack, Moritz K.; Ljung, Karin; Friml, Jiří; et al.
Abstract : The phenylpropanoid cis-cinnamic acid is a natural auxin efflux inhibitor that promotes lateral root formation. Abstract: Auxin steers numerous physiological processes in plants, making the tight control of its endogenous levels and spatiotemporal distribution a necessity. This regulation is achieved by different mechanisms, including auxin biosynthesis, metabolic conversions, degradation, and transport. Here, we introduce cis-cinnamic acid ( c -CA) as a novel and unique addition to a small group of endogenous molecules affecting in planta auxin concentrations. c-CA is the photo-isomerization product of the phenylpropanoid pathway intermediate trans-CA ( t -CA). When grown on c -CA-containing medium, an evolutionary diverse set of plant species were shown to exhibit phenotypes characteristic for high auxin levels, including inhibition of primary root growth, induction of root hairs, and promotion of adventitious and lateral rooting. By molecular docking and receptor binding assays, we showed that c -CA itself is neither an auxin nor an anti-auxin, and auxin profiling data revealed that c -CA does not significantly interfere with auxin biosynthesis. Single cell-based auxin accumulation assays showed that c -CA, and not t -CA, is a potent inhibitor of auxin efflux. Auxin signaling reporters detected changes in spatiotemporal distribution of the auxin response along the root of c -CA-treated plants, and long-distance auxin transport assays showed no inhibition of rootward auxin transport. Overall, these results suggest that the phenotypes of c -CA-treated plants are the consequence of a local change in auxin accumulation, induced by the inhibition of auxin efflux. This work reveals a novel mechanism how plants may regulate auxin levels and adds a novel, naturally occurring molecule to the chemical toolbox for the studies of auxin homeostasis.